A propensity score matched analysis of COVID-19 ongoing symptoms in primary medical staff members with different levels of stress in Jiangsu Province, China - Hualing Chen; Yongjie Zhang; Yongkang Qian; Ya Shen; Haijian Guo; Rongji Ma; Beier Lu; Pengcheng Miao; Biyun Xu; Jinshui Xu; Bingwei Chen (Heliyon, 2024)
Objective: Ongoing symptoms which originated from coronavirus disease 2019 (COVID-19) infections threaten the health of a broad population of patients. With recent changes in COVID-19 control measures in China, medical staff members are currently experiencing a high level of stress. This study aimed to investigate the prevalence of ongoing symptomatic COVID-19 and explore the potential association between stress and ongoing COVID symptoms. Methods: From January 17th to February 2, 2023, primary medical staff members in Jiangsu Province were surveyed using a self-designed questionnaire. Univariate multinomial logistic analysis was used to illustrate the relationship between stress and ongoing symptoms after matching the low- and high-stress groups in a 1:1 ratio based on propensity scores. Results: Analysis revealed that 14.83 % (3785/25,516) of primary medical staff members infected with COVID-19 experienced ongoing symptoms, the most common of which included cough (9.51 %), dyspnea (9.51 %), sleep problems (4.40 %), anxiety (2.29 %), and reproductive system symptoms (1.89 %). In matched patients, higher stress levels were associated with a greater risk of ongoing symptoms than in patients without ongoing symptoms for 14 of the 15 reported symptoms in this study (odds ratios [ORs] > 1 and P < 0.05). Moreover, higher levels of stress were associated with a greater risk of more ongoing symptoms, and the overall ORs increased with the number of symptoms (ORs >1 and P < 0.05). Conclusion: To mitigate the possibility of experiencing ongoing symptoms, healthcare organizations and local authority agencies should institute helpful measures to decrease stress levels such as medical staff augmentation and enabling all staff to have a reasonable work-life balance.